MINI-CURSO "BIOLOGIA FORENSE: A CIÊNCIA DESVENDANDO O CRIME" - DISCUTINDO TECNOLOGIA E CIÊNCIA EM SALA DE AULA - Yngrid Garay Berriel; Adriane Yumi Babá; Gabrielle Ossucci; Dulcinéia Ester Pagani Gianotto (Universidade do Oeste Paulista, 2011)
Forensic Biology is applied to criminal investigations every day. Because of its appeal to human curiosity, it has been largely explored by TV series. Aiming to supply the students with an up-to-date subject, uncommonly discussed in Biology classes, an opportunity has emerged of presenting a short course on Forensic Biology to 2nd and 3rd grade students of a High School in Maringá, Brazil. In order to get the students to understand the importance of training experts in this area of knowledge and how the latter behave on a crime scene, various didactics activities have been performed including practices and teamwork, rising of hypothesis and discussions which, according to those attending, were essential on developing the knowledge acquired during the course. The debate on the technologies used by the Forensic Sciences have turn up efficient when building knowledge related to Biology and other areas which have been approached in the course.